Inovasi Dalam Manajemen Perkantoran: Membangun Budaya Organisasi Yang Kreatif dan Adaptif di MTS Al-Washliyah Kolam - Afrizal Rambe; Liwa Ul Hamdi Silalahi; Jainatin Halomoan Harahap; Yudha Pratama Nasution; Tengku Darmansah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the implementation of innovative office management practices at MTs Al Washliyah Kolam with a focus on creating a creative and adaptive organisational culture. This research uses qualitative research methods, with interview techniques as data collection. The results of this study indicate that the implementation of an open and transparent management system and promoting effective two-way communication are important factors in encouraging a creative and adaptive organisational culture. Specifically, the study found that implementing an office management structure that reduces hierarchy and encourages cross-disciplinary teamwork can increase employee engagement, creativity and innovation. Furthermore, this research shows that developing a learning organisation culture that encourages continuous learning and sharing is essential to support innovation and adaptability. The results of this study provide valuable information for organisations looking to create a creative and adaptive organisational culture.